2021
DOI: 10.3892/wasj.2021.121
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inflammasomes: A possible therapeutic approach for periodontal disease (Review)

Abstract: Inflammasomes are cytosolic multimeric protein complexes that typically comprise a sensor, an adaptor and the zymogen, procaspase-1. Inflammasomes are a central hub for signaling and the regulation of innate immunity. An inflammasome assembles in response to a diverse range of pathogen-associated molecular patterns or danger-associated molecular patterns. Inflammasomes further induce the maturation of interleukin (IL)-1β and 18 through the proteolytic cleavage of pro-IL-1β and pro-IL-18. A number of previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Metformin, an oral antidiabetic drug, exhibits anti-inflammatory effects by reducing the activity of inflammasomes containing NLRP3, suggesting that anti-inflammatory drugs may be useful in the prevention and treatment of periodontal disease [ 42 ]. In addition, it has been reported that many drugs, such as allopurinol and nicotinamide riboside, inhibit intracellular signaling, and pralnacasan and emricasan inhibit caspase-1, and that many drugs act on various stages of the inflammatory reaction to exhibit anti-inflammatory responses [ 43 ]. However, it is not easy to introduce these anti-inflammatory drugs in rural Africa and distribute them in a short period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, an oral antidiabetic drug, exhibits anti-inflammatory effects by reducing the activity of inflammasomes containing NLRP3, suggesting that anti-inflammatory drugs may be useful in the prevention and treatment of periodontal disease [ 42 ]. In addition, it has been reported that many drugs, such as allopurinol and nicotinamide riboside, inhibit intracellular signaling, and pralnacasan and emricasan inhibit caspase-1, and that many drugs act on various stages of the inflammatory reaction to exhibit anti-inflammatory responses [ 43 ]. However, it is not easy to introduce these anti-inflammatory drugs in rural Africa and distribute them in a short period.…”
Section: Discussionmentioning
confidence: 99%
“…43.8%) and 86 females (56.2%). Three pairs of twins (3/156: 1.9%) were born, but they were not included in this table GA gestational age, BW birth weight a One participant who delivered a male newborn did not answer the questionnaire…”
mentioning
confidence: 97%
“…As a homeostatic checkpoint, inflammasomes control the degree of inflammation in both health and disease. Having a better understanding of the various methods that can be used to control an excessive inflammatory response at the cellular and molecular level may help to develop treatments and preventative measures that are more successful in treating periodontal disease and the systemic diseases that are linked to it (21)(22)(23).…”
Section: The Role Of Inflammasomes In the Pathogenesis Of Periodontitismentioning
confidence: 99%
“…Inflammasomes play a role in the control of inflammation in both healthy and diseased individuals. A better understanding of the various methods that can be employed to control excessive inflammatory responses at the cellular and molecular levels may help develop treatments and preventative measures that are more successful in treating periodontal and systemic diseases linked to it (21)(22)(23).…”
Section: Inflammasomes Play An Essential Role In the E229mentioning
confidence: 99%